Factors associated with low levels of lumbar strength in adolescents in Southern Brazil - Silva,Diego Augusto Santos (2014)
OBJECTIVE: To determine the prevalence and factors associated with low levels of lumbar strength in adolescents.METHOD: This was a cross-sectional study involving 601 adolescents, aged 14 to 17 years, enrolled in public schools in the western region of Santa Catarina State - Southern Brazil. Lumbar strength was analyzed by the lumbar extension test developed by the Canadian Society of Exercise Physiology, which proposes different cutoffs for boys and girls. Independent variables were sex, age, socioeconomic status, dietary habits, alcohol consumption, physical activity, and aerobic fitness. For data analysis, univariate and multivariate logistic regression were used, with significance level of 5%.RESULTS: The prevalence of low levels of lumbar strength was 27.3%. The population subgroups most likely to present low levels of lumbar strength were females (OR: 1.54, 95% CI : 1.06 to 2.23), adolescents with low levels of aerobic fitness (OR: 2.10, 95% CI: 1.41 to 3.11) and the overweight (OR: 2.28, 95% CI: 1.35 to 3.81).CONCLUSION: Almost one-third of the studied students have low levels of lumbar strength. Interventions in the school population should be taken with special attention to female adolescents, those with low levels of aerobic fitness, and those with overweight, as these population subgroups were most likely to demostrate low levels of lumbar strength.